Liquidity commonality on National Stock Exchange: size and sector effect. Issue 14 (16th August 2021) - Kumar, Suraj; Prasanna, Krishna
ABSTRACT: This study investigates the sources of liquidity commonality in an emerging Asian market. Specifically, the demand side and supply side factors were tested in an order-driven Indian stock market. The results indicate that growth in the industrial production and bank credit reflecting the supply side variables are found to have significant influence on liquidity commonality. However, compare to the supply side, demand side factors reflecting the trading behaviour of domestic and foreign institutional investors exhibited higher influence. Study has further extended the literature by investigating the size and sectorial effects and found heterogeneous impact on commonality.